The Role of Political Elites in the Development of Politics of Memory in the Baltic States - Smirnov Vadim (Baltic Region, 2015)
The article focuses on multiple cases of the politicization of history by the Baltic political elites. Three states of development of politics of memory in the Baltic States are identified. Problems of political exploitation of the past are scrutinized in the context of political life and international relations. It is concluded that the narratives of the past where nazi and Soviet legacies are equated are actively promoted on the pan-European level. Elites of the Baltic States play a salient role in this process and enhance ties with the elites of the Eastern Europe, expert and political communities of the Western Europe and USA. The dominant trends in the development of the historical politics in the Baltic countries are the administrative and legislative instruments for approval of the preferred narratives of the past, as well as an active political work at the international level aimed at the inclusion of the Baltic narratives of the past into the European politics of memory. Historical politics of the Baltic States shows the Baltic countries as the victims of "two totalitarianisms" ("Nazi and Soviet occupation"), and this point of view is widely used as a foreign policy tool. The politicization of the "anti-totalitarianism" issue is now a popular foreign policy tool that not only serves the interests of the Baltic and Eastern European politicians, but also finds ideological supporters in Western Europe and the United States.